Atividade antioxidante dos óleos essenciais de genótipos de Croton grewioides Baill, Croton tetradenius Baill e seus compostos majoritários - Oliveira, Sara Dayan da Silva (2018)
The Croton grewioides and Croton tetradenius species, popularly known as "marmeleiro" and "velaminho", are endemic to the Caatinga dry forest region in northeastern Brazil. These two species are widely used in folk medicine because they have many different biological activities. However, in general, there is a lack of information on the antioxidant activities of the Croton genus, as well as with a great absence of knowledge regarding the two aforementioned species. Therefore, this work has aimed at evaluating the antioxidant potential of the essential oils and the major compounds of the C. grewioides and C. tetradenius species. The essential oils were obtained by hydrodistillation and they were analyzed chemically in GC-MS-ICD terms. The CGR104, CGR106, CGR112 and CGR126 accessions of C. grewioides were obtained from the Germplasm Active Bank of the Federal University of Sergipe, Brazil. The accessions of C. tetradenius (CTE13, CTE31, CTE42 and CTE53) were collected from native populations in the State of Sergipe. The antioxidant capacities of the essential oils and their respective isolated constituents were determined by the capturing of the DPPH and ABTS radicals, as well as by the Ferric Reducing Ability (FRAP) assay and the β-carotene-linoleic acid co-oxidation test. In the chemical analyzes, 21 compounds were identified in the accessions of the C. grewioides species, whose majorities in the CGR104 accession were as follows: (Z) -iso-morpholol (38.74%), (E) -isoosmorhizol (24.74%), (E) methyl isoeugenol (11.38%) and (Z) -methyl isoeugenol (9.34%); in the CGR106 accession, they were methyl chavicol (59.85%) and eugenol (25.51%); in the CGR112 accession, it was methyl eugenol (85.58%); and in the CGR126 accession, they were methyl eugenol (45.97%) and eugenol (42.68%). A total of 37 compounds were identified in the accessions of the C. tetradenius species, namely, trans-ascaridol (24.09%), ρ-cymene (22.29%), α-pinene (11.97%), camphor (8.71%), α (8.37%), 1.8-cineol (8.18%) and γ-terpinene (6.84%). The essential oils of the C. grewioides and C. tetradenius species showed antioxidant potentials in all of the tested methods, with an emphasis on the CGR106 and CTE31 essential oils, which presented the highest antioxidant activities, except for β-carotene, where the essential oils of CGR126 and CTE31 were superior. There was a much greater efficiency of the essential oils of the C. grewioides species among all of the isolated compounds that were tested, with the compound eugenol showing the greatest antioxidant activity. In the C. tetradenius species, the isolated compounds only showed minor antioxidant activities when compared to its essential oils. Based upon the results that were obtained, all of the essential oils of the C. grewioides and C. tetradenius species presented a positive antioxidant potential. This could support future research aimed at, for example, the genetic improvements that are directed at the development of products with an antioxidant action.